Crystallization of fragment D from human fibrinogen. - Everse, S. J. (Cold Spring Harbor Laboratory Press, 1995)
Fragment D from human fibrinogen has been crystallized. The fragment, which is composed of three disulfide-linked chains (alpha' beta' gamma' = 88,000), was generated with either plasmin or mild trypsin digestion. The crystals diffracted out to 3.5 A; the space group is P2(1), unit cell dimensions a = 108 A, b = 48 A, c = 167 A, beta = 106 degrees. Fragment D was also co-crystallized with the ligand GPRP-amide, in which case the space group is consistent with P212121, unit cell dimensions a = 476 A, b = 82 A, c = 432 A.